Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/750208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long distance retrograde degeneration of the retino-geniculo-cortical pathway in homonymous hemianopia

Abstract: Long-distance retrograde degeneration of the retino-geniculo-cortical pathway has been described in humans and animal models following injury to the brain. In this study, we used optical coherence tomography (OCT) to measure the severity and timing of retrograde degeneration after post-chiasmal visual pathway lesions in patients with homonymous hemianopia. We performed a retrospective study of 69 patients with homonymous hemianopia and analyzed high quality OCT macular ganglion cell complex (GCC) and retinal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Such a pattern is suggestive of initial resolution of cytotoxic edema and inflammation, followed by the development and increasing impact of trans-synaptic retrograde degeneration. [15][16][17][18][19][20][21][22][23][24][25] In trans-synaptic retrograde degeneration, the loss of targets in primary visual cortex leads sequentially to the death of relay neurons in the ipsilesional dorsal lateral geniculate nucleus of the thalamus, and then to the loss of retinal ganglion cells in the affected portion of both eyes. [15][16][17][18][19][20][21][22][23][24][25] Our results are thus consistent with the temporality of trans-synaptic retrograde degeneration: experiments in non-human primates have found histological evidence of degenerative changes as early as 100 days after occipital lesioning, 18 and optical coherence tomography in humans has found thinning of the retinal nerve fiber layer in the affected retinal region as early as one month post-stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a pattern is suggestive of initial resolution of cytotoxic edema and inflammation, followed by the development and increasing impact of trans-synaptic retrograde degeneration. [15][16][17][18][19][20][21][22][23][24][25] In trans-synaptic retrograde degeneration, the loss of targets in primary visual cortex leads sequentially to the death of relay neurons in the ipsilesional dorsal lateral geniculate nucleus of the thalamus, and then to the loss of retinal ganglion cells in the affected portion of both eyes. [15][16][17][18][19][20][21][22][23][24][25] Our results are thus consistent with the temporality of trans-synaptic retrograde degeneration: experiments in non-human primates have found histological evidence of degenerative changes as early as 100 days after occipital lesioning, 18 and optical coherence tomography in humans has found thinning of the retinal nerve fiber layer in the affected retinal region as early as one month post-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25] In trans-synaptic retrograde degeneration, the loss of targets in primary visual cortex leads sequentially to the death of relay neurons in the ipsilesional dorsal lateral geniculate nucleus of the thalamus, and then to the loss of retinal ganglion cells in the affected portion of both eyes. [15][16][17][18][19][20][21][22][23][24][25] Our results are thus consistent with the temporality of trans-synaptic retrograde degeneration: experiments in non-human primates have found histological evidence of degenerative changes as early as 100 days after occipital lesioning, 18 and optical coherence tomography in humans has found thinning of the retinal nerve fiber layer in the affected retinal region as early as one month post-stroke. 20 Loss of these early visual sensory substrates could constrain the effectiveness of visual restoration treatments 34,35 ; a recent study of vision training therapy after stroke found that training-induced recovery of visual fields in the chronic post-stroke period was indeed limited by shrinkage of the optic tracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation